The Influence Of Family Economic Conditions on The Learning Achievement Of Campus II Students Of Andalas University - Desri, Suryatman; Ikhsan, Shohibul (Journal of Ageing And Family, 2023)
Education is something that is very important for humans so that one day they can face obstacles and challenges. The success of a person in carrying out education is influenced by himself because of his interests, and can also be influenced by external factors such as the environment and family conditions. The purpose of this study was to determine the effect of family economic factors on student achievement at Campus II Andalas University. The type of research used is qualitative using secondary data, analyzing scientific article literature and primary data by conducting direct interviews with students of Campus II Andalas University. The results showed that the economic conditions of the family did not have a major effect on student achievement at Campus II Unand. From these results it is hoped that it will be useful for internal parties such as BEM and other organizations to assist students in dealing with problems in education. Keywords: Economics, Learning Achievement, Family